Absorbing aerosol‐induced change in the early monsoon Arabian Sea low‐level jet: Modeled transfer from anomalous heating to nondivergent kinetic energy. Issue 22 (27th November 2013) - Martin, Andrew C.; Krishnamurti, T. N.; Lau, William K. M.
<x xml:space="preserve">Abstract</x> [1] This study examines the impact of anomalous differential generation of available potential energy by absorbing aerosols on the transition and early active phases of the South Asian summer monsoon. Aerosol direct and indirect radiative forcings can modify tropospheric temperature profiles through direct absorption, scattering, and extended cloud lifetimes. Recent studies have suggested that over monthly and seasonal time scales, these effects can lead to modified flow and rainfall regimes in the South Asian monsoon region. Of special interest is the covariance of heating and temperature prior to active monsoon onset. It can be shown that anomalous generation of available potential energy due to absorption of shortwave radiation by aerosols can impact the cascade of energy from the local Hadley circulation to the monsoon nondivergent flow. In order to quantify the potential impact of aerosol radiative forcing and the resulting changes in monsoon onset timing and intensity, an ensemble of Weather Research and Forecasting with Chemistry regional weather and chemistry model forecasts are created for the South Asian summer monsoon region during May, June, and July. The forecasts including shortwave absorption by aerosol are compared to control forecasts in which aerosols only scatter shortwave radiation. The evolution of irrotational and nondivergent kinetic energy, generation of available potential energy and rainfall are presented. It is found that the ensemble with aerosol shortwave absorption contains on average a more intense dynamical onset over South India which is statistically significant compared to the ensemble variability. The more intense monsoon onset is related to a more intense Arabian Sea low‐level jet. In the ensemble with shortwave absorption by aerosol, the early season monsoon rainfall is diminished over South India and enhanced over the Northeastern Indian states.